Low pressure pain thresholds are associated with, but does not predispose for, low back pain - O’Neill, Søren (Springer-Verlag, 2011)
Chronic pain is often associated with hyperalgesia in cross-sectional studies. In the present study, a random cohort of 40-year-old individuals (n = 264) from the general population was assessed for low back pain (LBP) status and pressure pain threshold (PPT), with follow-up assessment 4 and 8 years later. Low PPT at baseline as a potential risk factor for the development of LBP was investigated longitudinally and the association between LBP and hyperalgesia was studied cross-sectionally at baseline and 8-year follow-up. Generalized (p  < 0.03) and localized pressure hyperalgesia (p < 0.02) was found in participants with long-lasting LBP, but not with recent LBP (p > 0.08). Of the participants without recent or long-lasting LBP, those with a low PPT at baseline (lower 10% percentile) had no increased risk of developing LBP (p > 0.05). The findings indicate that PPT decreases as a consequence of long-lasting pain, whereas a low PPT seems not to constitute a separate risk factor for the development of LBP. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00586-011-1796-4) contains supplementary material, which is available to authorized users.